2010
DOI: 10.2519/jospt.2010.3095
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Shoulder Musculature During Pendulum Exercises and Light Activities

Abstract: Study Design Prospective, single-group, repeated-measures design. Objectives To evaluate electromyographic (EMG) signal amplitude in the supraspinatus, infraspinatus, and deltoid muscles during pendulum exercises and light activities in a group of healthy subjects. Background There are numerous rehabilitation protocols used after rotator cuff repair. One of the most commonly used exercises in these protocols is the pendulum. Patients can easily perform these exercises incorrectly, and may also perform light ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 46 publications
(45 reference statements)
3
44
0
6
Order By: Relevance
“…Similar differences were reported for activities for daily living and shoulder exercises. For example, a previous study reported differences between typing and drinking tasks to be approximately 2% of MVIC for middle deltoid, and approximately 6% MVIC for infraspinatus muscle (Long et al , 2010). Another study reported differences of approximately 1% MVIC for supraspinatus muscle, when comparing the full and empty can exercises (Reinold et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similar differences were reported for activities for daily living and shoulder exercises. For example, a previous study reported differences between typing and drinking tasks to be approximately 2% of MVIC for middle deltoid, and approximately 6% MVIC for infraspinatus muscle (Long et al , 2010). Another study reported differences of approximately 1% MVIC for supraspinatus muscle, when comparing the full and empty can exercises (Reinold et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As electromyographic (EMG) activity is low with these exercises, they were considered representative of passive exercise (Dockery, Wright, & LaStayo, 1998;Long et al, 2010;McCann, Wootten, Kadaba, & Bigliani, 1993). Active exercise was defined as "patient-generated movement" whereas resisted exercise was defined as movement undertaken with load applied (Petty, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Small pendular exercises (20cm in diameter) performed in a position of trunk flexion generate less than 10% maximal voluntary contraction (MVC) of supraspinatus, whereas large, incorrectly performed pendular exercises can generate more than 15% of MVC of supraspinatus (Long et al, 2010). The ASSET consensus statement recommends protected passive ROM during the first 6 weeks after rotator cuff repair of small to medium sized tears (< 4cm), with EMG activity of 15% (Thigpen et al, 2016).…”
Section: Passive Exercisementioning
confidence: 99%
“…Electromyographic (EMG) analysis of the supraspinatus confirms that therapist assisted shoulder elevation and external rotation, and pendulums performed by the patient are truly passive as these motions elicit activity similar to resting levels [21•]. However, EMG data reveals that with incorrectly performed pendulums moderate activity of the supraspinatus is generated and therefore may be avoided in early rehabilitation programs to minimize chance of patient error [22]. When correctly performing pendulums, the patients position themselves slightly bent over, supported with their non-surgical arm.…”
Section: Range Of Motionmentioning
confidence: 99%